(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe learning motivation and identify associated factors among nursing students at Pham Ngoc Thach University of Medicine. Subjects and Methods: A descriptive cross-sectional study was conducted on 266 nursing students at Pham Ngoc Thach University of Medicine in 2024. Learning motivation was assessed using the Academic Motivation Scale (AMS-C28)—specifically the Vietnamese version translated by Nguyen Van Tuan et al.—which demonstrated a Cronbach’s alpha coefficient of 0.912. Results: The proportion of nursing students with good learning motivation was 72.5%. No statistically significant associations were found between learning motivation and gender, academic year, or the desire to pursue postgraduate studies (p > 0.05). Conclusion: The majority of nursing students possess good learning motivation. Further research is needed to clarify associated factors and provide a basis for developing appropriate interventions.